Study on chloride ion erosion resistance of recycled aggregate concrete based on an improved TOPSIS model integrating entropy weight and AHP - Yali Cao; Wenbang Zhu; Xinjie Wang; Chuikan Li; Ruiming Liu; Dali Zhang; Xiumei Zheng; Baochen Tang (PLoS ONE, 2026)
Recycled coarse aggregate (RA) is prone to deteriorating the performance of recycled aggregate concrete (RAC) due to inherent defects such as adhered old cement paste and internal micro – cracks, while calcined layered double hydroxides (CLDHs) exhibit significant potential for enhancing concrete performance. However, the synergistic mechanism between CLDHs and RA remains unclear. To address this, this study employs compressive strength, chloride ion (Cl - ) penetrability, X - ray diffraction (XRD), scanning electron microscopy (SEM), and nuclear magnetic resonance (NMR) to investigate the effects of varying CLDHs content (0%, 1%, 3%, 6%) and RA replacement rates (0%, 10%, 20%, 30%) on the mechanical properties, chloride ion permeability resistance, and microstructure of RAC. Results indicate that an appropriate combination of CLDHs and RA significantly improves RAC performance: the mix with 1% CLDHs and 20% RA increased the 28 d compressive strength by 10.3% compared to the reference group, while the combination of 3% CLDHs and 30% RA enhanced chloride ion penetration resistance by 19.1%, with electrical flux as low as approximately 1135 C, achieving a “low” permeability rating. Microstructural analysis confirms that the synergistic interaction of suitable CLDHs and RA promotes the formation of dense flocculent C – S – H gel, fills pores, reduces the proportion of harmful pores, increases the ratio of gel pores, thereby optimizing pore structure and enhancing system compactness. Additionally, it delays crack initiation and propagation, resulting in no penetrating cracks upon specimen failure. Based on these findings, an improved TOPSIS comprehensive evaluation model integrating the entropy weight (EW) method and the Analytic Hierarchy Process (AHP) was developed. This model systematically evaluates the chloride ion erosion resistance of Recycled Aggregate Concrete (RAC) by synthesizing multidimensional indicators such as compressive strength, electrical flux, and pore structure, thereby overcoming the limitation of single-factor weighting inherent in the entropy weight method. Concurrently, through economic analysis, an adjustable decision-making framework for RAC mix proportion selection under various corrosive environments has been proposed. This study elucidates the mechanism by which CLDHs and RA synergistically improve RAC performance, providing a theoretical foundation and methodological support for the engineering application of recycled concrete in aggressive environments.